Tawfeeq Wehbe Man of Science and Politics in Iraq: (Historical Study) - Tawfeeq, Israa Talib (Al-Adab Journal, 2021)
Twfiq Wahbi akurdish_Iraqi officer he was an educated person and he was also entering and researcher in Kurdish Language. He was one of the establishers of Iraqi army in 6 January in 1921.He went to the civil work and he held Leading positions in the modern Iraqi country. He worked as a minister of economy and education then a minister of social affairs. He had a lot of writings and he considered one of the important references in the types of art, Language, science, news, travelling and men Levels. but he had Less Literary and intellectual writings though he was distinguished for his Linguistic and Literary abilities. He had a great role in designing, the modern Kurdish alphabetical and it's written in Arabic Letters. He was one of the establishers of Iraqi scientific complex and he great interest in culture, art and social affairs through his foundation or participation in the social clubs that visited by the men of policy, science and art. He had clear touches and conti but ion in the fields of media and art. He mastered a lot of languages ((cold and new one)) example Arabic Kurdish, English, Carmen, Turkish and Persian (old and new). The cultural side played a great role in completing and shaping his character and the great efforts he presented for the Iraqi culture in general and the Kurdish one especially. as a result, He had a clear role in finding a number of new Letters and putting the grammar of Kurdish Language .so Wahbi was the first Kurdish man who fix the rules of writing Kurdish Language in Arabic Letters and putting special signs for it. Then his writings came in different Languages moreover his researches, studies and different assays.